Evaluating the Teaching Factory Model for Culinary Competency Development in Vocational Education: A Qualitative Study - Athi Aliyatus Sya’ni; Endang Wuryandini; I Made Sudana (Universitas Negeri Semarang, 2025)
In February 2025, the Central Statistics Agency reported that vocational school graduates had the highest unemployment rate based on education level. One of the causes is the delay in learning facilities in vocational schools in keeping up with industrial technological developments. To overcome this problem, vocational schools have implemented the Teaching Factory model to enhance the quality of education and align competencies with industrial needs. This study explores and analyzes the Teaching Factory's management of culinary arts competencies. The research subjects included the principal, vice principal, head of culinary arts competencies, and vocational teachers. The results showed that the Teaching Factory program planned included formulating plans, objectives, requirements, budgets, and evaluations. Organizations form teams according to competency units involving teachers and students. Staffing places personnel according to their expertise and organizes tasks to avoid overlap. Motivation is focused on students as the primary target, with teachers providing motivation. Supervision is done in real time to ensure activities are run according to standards. This study concludes that the Teaching Factory improves technical skills and develops discipline, responsibility, and work skills relevant to the industrial world